Development of a Book Borrowing & Returning System Using the Extreme Programming Method - MUHAMMAD RAIHAN MARSAQ; Andri Andri; Nyimas Sopiah; Nia Oktaviani (Journal of Information System and Artificial Intelligence, 2025)
Based on the researcher’s observations at the SMA Negeri 7 Palembang Library, the identified issues include errors in recording book loans and a lack of well-documented data. This problem arises because the book loan recording process relies solely on manual note-taking, which is relatively slow. Additionally, the library does not have a medium to inform students about its book collection, reducing students' interest in borrowing books. To address these issues, the author aims to develop a book borrowing information system to enhance the efficiency of book management and borrowing in the library while also providing students with information about the available book collection. This research employs the Extreme Programming system development methodology. The objective of this study is to build an information system for book borrowing and returning, which also serves as an informational medium for the library’s book collection at SMA Negeri 7 Palembang. The system is designed and developed as a web-based application using PHP as the programming language and MySQL as the database, with UML as the modeling tool. The research results show that the developed system can improve time efficiency in the book borrowing process by 75%. This conclusion is based on the fact that the borrowing process previously took an average of 20 minutes before using the system, but it now takes less than 5 minutes with the system. Therefore, the developed system will significantly assist in the management and borrowing process at the SMA Negeri 7 Palembang Library.